Permanent deformation resistance of fibre reinforced asphalt mixture - Mohammed, Monketh (2019)
The loss of strength in road pavements due to high traffic loads, increasing number of road users, severe climate conditions and moisture is a recurring problem, creating distress such as ravelling, fatigue and permanent deformation. It is, therefore, important to find a way to improve or at least delay the loss of strength in asphalt mixtures. Such an improvement would lead to longer service life and a more comfortable drive for road users. This research develops a fundamental understanding of the effect of fibre on binder and asphalt mortar, leading to an evaluation of fibre reinforced dense asphalt mixtures. It determines which fibre type provides the best, most cost-effective performance improvement in terms of rutting and cracking resistance. The study also gives an understanding of the factors that affect the behaviour of fibres in the mix, such as fibre surface texture, distribution and fibre length. The dynamic shear rheological test results of complex modulus and phase angle master curves indicate that the modification mechanism of fibre reinforcement consists of three dimensional networks within the mastic or the mortar as shown in scanning electronic microscope images. These three dimensional networks increase the stiffness and elastic properties of the modified mastic or mortar, mainly at high temperatures (45-70)℃. Under these circumstances, the viscosity of mastic and/or mortar is low enough to allow the fibre entanglement to control the rheological properties of fibre reinforced materials. The modification mechanisms of cellulose fibre also consist of a possible chemical change by absorption/adsorption of bitumen fractions that increases the stiffness and elasticity of the binder, mainly at high temperatures (45-70)℃. This study assesses the potential modification of the binder due to the presence of fibres, by means of work of cohesion and work of adhesion calculations, based on surface energy parameters. The study also evaluates the influence of different filler to bitumen ratios and fibre percentages on pull-off tensile strength. The test results indicate that the fibres enhance the pull-off tensile strength of the mortar, in addition to changing the failure mode from cohesive to hybrid, implying an improvement in the cohesive strength of the mortar. This thesis examines the relative performance of the asphalt mixture modified with different fibre types and contents in terms of the main distress types related to flexible pavement. Also, fibre distribution and orientation in the asphalt mixture was explored in this study. The results show that fibre has a significant influence on the performance; the irrecoverable strain and peak strain in the multiple stress creep recovery test both decrease; the stiffness increases; the recovery percentage increases; and, the accumulated strain decreases. The repeated load axial test and immersed Hamburg wheel tracking test indicate a significant improvement in permanent deformation resistance of fibre modified mixtures compared to the unmodified case. Also, the test results show that fibres have a notable impact on the stiffness modulus and fracture toughness of asphalt mixtures at the 20℃ test temperature. Moreover, fibres give slightly improved fatigue life of asphalt mixtures, mainly at low strain values. However, results indicate that there is no clear influence of fibres on the indirect tensile strength and moisture damage of asphalt mixture at the 20℃ test temperature. A comparison of the pavement analysis and design results of control and fibre reinforced asphalt mixtures reveal that adding fibre to the asphalt mixture results in an increase in pavement life mainly for cellulose and steel fibres.